2023
DOI: 10.3390/cancers15061703
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Chondrosarcoma: From Characteristic to Challenging Imaging Findings

Abstract: Chondrosarcomas can be classified into various forms according to the presence or absence of a precursor lesion, location, and histological subtype. The new 2020 World Health Organization (WHO) Classification of Tumors of Soft Tissue and Bone classifies chondrogenic bone tumors as benign, intermediate (locally aggressive), or malignant, and separates atypical cartilaginous tumors (ACTs) and chondrosarcoma grade 1 (CS1) as intermediate and malignant tumors. respectively. Furthermore, the classification categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 114 publications
0
31
0
3
Order By: Relevance
“…Chondroid tumors are known to be highly heterogeneous, which increases the risk of biopsy sampling errors, ultimately leading to improper treatment. [1][2][3][4][5] Thus, the tumor must be graded on the areas demonstrating the highest grade. 6 We previously reported that osteoblastic activity on quantitative bone SPECT/CT might reflect biological feature of chondrosarcoma based on histologic characteristics of permeative growth pattern.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Chondroid tumors are known to be highly heterogeneous, which increases the risk of biopsy sampling errors, ultimately leading to improper treatment. [1][2][3][4][5] Thus, the tumor must be graded on the areas demonstrating the highest grade. 6 We previously reported that osteoblastic activity on quantitative bone SPECT/CT might reflect biological feature of chondrosarcoma based on histologic characteristics of permeative growth pattern.…”
Section: Figurementioning
confidence: 99%
“…In the wide-excision specimen, slides ( C and D ) show more hypercellular and clustered tumor cells, implying grade II chondrosarcoma. Chondroid tumors are known to be highly heterogeneous, which increases the risk of biopsy sampling errors, ultimately leading to improper treatment 1–5 . Thus, the tumor must be graded on the areas demonstrating the highest grade 6 .…”
mentioning
confidence: 99%
“…4,5 The World Health Organization classifies chondrosarcomas as benign, intermediate, or malignant cartilaginous tumors. 6 Conventional chondrosarcomas account for more than 80% of chondrosarcomas and include the central, periosteal, and peripheral subgroups. 7 Chondrosarcomas are a group of different types of malignancies with distinct histopathological features characterized by the production of cartilage matrix.…”
Section: Introductionmentioning
confidence: 99%
“…У самостійну форму була виділена в 1930 р. Phemister. Вона є третьою за поширеністю серед великих первинних злоякісних пухлин кісток після множинної мієломи й остеосаркоми, становить 20-25 % від загальної кількості усіх пухлин кістково-м'язової системи та характеризується початковим розвитком із хрящових клітин [2][3][4]. Доведено, що на ХС припадає близько 3,6 % щорічної захворюваності на всі первинні злоякісні пухлини та 20-30 % первинних злоякісних пухлин кісток у США [5].…”
unclassified
“…Як зазначено вище, ХС розрізняють за виникненням (первинні та вторинні), локалізацією (центральні -усередині інтрамедулярної порожнини, периферичні -усередині кришки хряща попередньо існуючої остеохондроми, періостальні -юкстакортикальні, на поверхні кістки) [3,4,18]. Подальша класифікація ХС заснована на гістологічних підтипах пухлини, включаючи звичайні (І-ІІІ ступені), світлоклітинні, мезенхімальні та дедиференційовані ХС [19,20].…”
unclassified